2021
DOI: 10.1093/brain/awab018
|View full text |Cite
|
Sign up to set email alerts
|

A serum microRNA sequence reveals fragile X protein pathology in amyotrophic lateral sclerosis

Abstract: Knowledge about converging disease mechanisms in the heterogeneous syndrome amyotrophic lateral sclerosis (ALS) is rare, but may lead to therapies effective in most ALS cases. Previously, we identified serum microRNAs downregulated in familial ALS, the majority of sporadic ALS patients, but also in presymptomatic mutation carriers. A 5-nucleotide sequence motif (GDCGG; D = G, A or U) was strongly enriched in these ALS-related microRNAs. We hypothesized that deregulation of protein(s) binding predominantly to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…We identified several genes connected to RNA pol II transcription strongly downregulated by Combo, including YBX1 and FXR1 . RNA pol II transcription-associated DNA damage is increased in ALS (83), and these two specific genes are dysregulated and affect RNA homeostasis and transcriptional activity in sALS (84, 85). Lastly, Combo modulates innate immune pathways involving cGAS/STING signaling, which has been reported to be activated in ALS (42).…”
Section: Discussionmentioning
confidence: 99%
“…We identified several genes connected to RNA pol II transcription strongly downregulated by Combo, including YBX1 and FXR1 . RNA pol II transcription-associated DNA damage is increased in ALS (83), and these two specific genes are dysregulated and affect RNA homeostasis and transcriptional activity in sALS (84, 85). Lastly, Combo modulates innate immune pathways involving cGAS/STING signaling, which has been reported to be activated in ALS (42).…”
Section: Discussionmentioning
confidence: 99%
“…Both FXR1 and FXR2 were found to interact directly with ALS-related microRNAs via GDCGG motif-specific binding, and FXR1 was found specifically to co-aggregate with FUS in motor neurons. This implies a broader role for the family of Fragile X-related proteins in neuromuscular diseases beyond structural myopathies 10. Variants in FXR1 have been associated with several neuropsychiatric diseases, notably insomnia, bipolar disorder and schizophrenia 11 12.…”
Section: Discussionmentioning
confidence: 99%
“…Again, a whole transcriptome profiling, combined with subcellular fractionation analysis of NSC-34 human SOD1 cells, revealed that miR-18b-5p heads a complex gene pathway made up of Hif1α, Mef2c, miR-206, Mctp1, and Rarb, with a downstream effect on cell apoptosis [ 102 ]. A very original contribution recently came from Freischmidt and colleagues [ 103 ] who identified, by proteomic and biochemical studies, the members of the fragile X protein family as interactors of a short sequence motif, enriched in a signature of previously identified ALS-related miRNAs [ 104 , 105 ].…”
Section: Noncoding Rna Landscapementioning
confidence: 99%
“…Again, a whole transcriptome profiling, combined with subcellular fractionation analysis of NSC-34 human SOD1 cells, revealed that miR-18b-5p heads a complex gene pathway made up of Hif1α, Mef2c, miR-206, Mctp1, and Rarb, with a downstream effect on cell apoptosis [102]. A very original contribution recently came from Freischmidt and colleagues [103] who identified, by proteomic and biochemical studies, the members of the fragile X protein [106], an RBP implicated in neural function and degeneration [107], and of proapoptotic targets such as p53. In concordance with this result, in the sALS wobbler mouse-a model displaying almost all clinical hallmarks of human ALS patients [108]-miRNA-375-3p downregulation resulted in inefficient p53 inhibition, increased production of reactive oxygen species, and induced apoptosis [109].…”
Section: Integrative Mirna-omics Studies In Alsmentioning
confidence: 99%